Determinants of Industrial Internet of Things Adoption in German Manufacturing Companies - Arnold, Christian; Voigt, Kai-Ingo (International Journal of Innovation and Technology Management, 2019)
This study aims at examining factors that determine the adoption of the Industrial Internet of Things (IIoT) by manufacturing companies applying the technology-organization-environment framework. Data of 197 German manufacturers are gathered by means of a survey questionnaire and tested using a logistic regression. This paper contributes to academic discussion by revealing determinants, which have a significant influence on the adoption of the IIoT: relative advantage associated with the IIoT, support by a company's top management, high levels of competition, and environmental uncertainty. The study provides important implications, both for research and practitioners, related to technology management in the context of the IIoT.
CRIS-Team Scopus Importer:2019-10-18
Keywords: German manufacturing companies; Industrial Internet of Things; Industrie 4.0; Industry 4.0; quantitative research; technology adoption